The Use Of Social Media In Guidance And Counseling Service Through Project Based Learning Activity (An Action Research With Guidance And Counseling Students of Universitas PGRI Palembang) - Ahmad RofiSuryahadikusumah; M. Ferdiansyah (Jurnal Dosen Universitas PGRI Palembang)
AbstrakResearch aims to improve student of guidance and counseling program’s ability in use social media as a relevant guidance media with a guidance and counseling services target, through the project based learning activities. Action research was chosen as the research method, so that students can participate reflect during designing media, managing social media, until received a response from followers of his social media. The research was conducted in six cycle developing and designing a media, executing, and evaluating. Result shown factors that contribute to the success of the program are: 1) content information must be engaged with lifestyle contextual, and adolescent's need, 2) share information in a simple way, 3) use trusted source for information, 4) requires daily language for the content, and 5) add some picture that embed with topic. Research outcome recommended to learning process of technology in counseling, or developing counseling's media at guidance and counseling program study.